2017
DOI: 10.1021/acs.jctc.7b00328
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Nature of Short-Range Excitonic Interactions in Light Harvesting Complexes and Organic Semiconductors

Abstract: Copies of full items can be used for personal research or study, educational, or not-for profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. Publisher's statement:"This document is the Accepted Manuscript version of a Published Work that appeared in final form in Journal of Chemical Theory and Computation. copyright © American Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 84 publications
3
26
0
Order By: Relevance
“…In summary, more efficient packing leads to improved charge carrier transport, higher mobilities 29 and short contact distances. [30][31][32][33] Factors which alter the packing of a material are strong dipole-dipole interactions, 34,35 degree of backbone planarity and steric locking of polymer backbones. 36,37 1.2.…”
Section: Charge Transport and Morphology Of N-type Organic Semiconductorsmentioning
confidence: 99%
“…In summary, more efficient packing leads to improved charge carrier transport, higher mobilities 29 and short contact distances. [30][31][32][33] Factors which alter the packing of a material are strong dipole-dipole interactions, 34,35 degree of backbone planarity and steric locking of polymer backbones. 36,37 1.2.…”
Section: Charge Transport and Morphology Of N-type Organic Semiconductorsmentioning
confidence: 99%
“…The largest difference is of 26 meV, which represents 25% of the greatest coupling (105 meV). It is expected that in cofacial dimers with couplings of such magnitude, the short‐range interactions should account for most of the coupling, making the use of a coupling scheme which accounts for exchange imperative …”
Section: Featuresmentioning
confidence: 99%
“…Ref. 23 found that when Coulombic coupling exceeds 70 meV in organic semiconductor materials and light-harvesting complexes, the exchange portion of the coupling always shares a sign with its electrostatic counterpart, thus increasing the total coupling. This is consistent with the deviation of the limiting behaviour of the total coupling from a Coulombic inverse law.…”
Section: Exciton Couplingmentioning
confidence: 99%